The use of new surface-modified poly(2-hydroxyethyl methacrylate) hydrogels in tissue engineering: treatment of the surface with fibronectin subunits versus Ac-CGGASIKVAVS-OH, cysteine, and 2-mercaptoethanol modification - Kubinová, Šárka; Horák, Daniel; Vaněček, Václav; Plichta, Zdeněk; Proks, Vladimír; Syková, Eva (Journal of biomedical materials research. Part A, 2014)
Superporous poly(2-hydroxyethyl methacrylate) is successfully used as a scaffold material for tissue engineering; however, it lacks functional groups that support cell adhesion. The objective of this study was to investigate the cell-adhesive properties of biomimetic ligands, such as laminin-derived Ac-CGGASIKVAVS-OH (SIKVAV) peptide and fibronectin subunits (Fn), as well as small molecules exemplified by 2-mercaptoethanol (ME) and cysteine (Cys), immobilized on a copolymer of 2-hydroxyethyl methacrylate (HEMA) with 2-aminoethyl methacrylate (AEMA) by a maleimide-thiol coupling reaction. The maleimide group was introduced to the P(HEMA-AEMA) hydrogels by the reaction of their amino groups with N-γ-maleimidobutyryl-oxysuccinimide ester (GMBS). Mesenchymal stem cells (MSCs) were used to investigate the cell adhesive properties of the modified hydrogels. A significantly larger area of cell growth as well as a higher cell density were found on Fn- and SIKVAV-modified hydrogels when compared to the ME- and Cys-modified supports or neat P(HEMA-AEMA). Moreover, Fn-modification strongly stimulated cell proliferation. The ability of MSCs to differentiate into adipocytes and osteoblasts was maintained on both Fn- and SIKVAV-modifications, but it was reduced on ME-modified hydrogels and neat P(HEMA-AEMA). The results show that the immobilization of SIKVAV and Fn-subunits onto superporous P(HEMA-AEMA) hydrogels via a GMBS coupling reaction improves cell adhesive properties. The high proliferative activity observed on Fn-modified hydrogels suggests that the immobilized Fn-subunits maintain their bioactivity and thus represent a promising tool for application in tissue engineering.
Keywords: Tissue Engineering; povrchové vlastnosti; fibronektiny; Hydrogels; cystein; Mercaptoethanol; buněčná diferenciace; IKVAV (Ile-Lys-Val-Ala-Val) peptide; fibronectin; hydrogely; tissue engineering; tkáňové inženýrství; krysa rodu Rattus; polyhydroxyethylmethakrylát; Animals; Microscopy, Electron, Scanning; Polyhydroxyethyl Methacrylate; zvířata; hydrogel; Surface Properties; Rats; merkaptoethanol; Peptides; scaffold; peptidy; Fibronectins; 2-hydroxyethyl methacrylate; mikroskopie elektronová rastrovací; Mesenchymal Stem Cells; Cysteine; Cell Differentiation; mezenchymální kmenové buňky